EPISTEMOLOGI SEBAGAI FUNDAMENTAL EKONOMI ISLAM - Meitia Ivanka; Nur Widya Ningsih (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Epistemology in the realm of Islamic economics refers to the perspective and knowledge methods applied to understand various economic dimensions by adhering to Islamic values ​​and principles. This epistemological concept includes an understanding of sources of knowledge, research methodology, and the framework of thinking used in analyzing economic phenomena. The aim of this journal is to conduct an in-depth analysis of epistemology as a basis for understanding Islamic economics. Within this framework, this research investigates various aspects related to epistemology in Islamic economics, involving understanding the basic sources of Islamic law, as well as exploring the benefits of epistemology as the main foundation in the context of Islamic economics.